AN ANALYSIS OF THE IMPACT OF SOME SOCIO-ECONOMIC VARIABLES IN REGULATING THE CULTIVATION AND MARKETING OF THE RICE CROP IN IRAQ - Noor.A.A; A.D.K AL-Hiyali; Muhammed. KH. M (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research was aimed to study the results of the application of agricultural legislation and the variables affecting compliance with such legislation, as well as knowing the role of agricultural legislation in supporting the agricultural policy steps in Iraq. The results showed that the variable of providing loans increases the probability of farmers’ commitment to the governmental agricultural plan to a large extent, amounting to about (28.7), and the variable of the sale price of the crop to the state has an impact on the probability of commitment to the plan at a degree of (1.02) greater than the chances of non-compliance with the agricultural plan, as well as the variable value of the returns achieved under The existence of government support to a degree or a fixed rate of (1) in favor of adhering to the agricultural plan. As for the farmers’ decision to market their crops to the state, it was found that the most influential variables were the commitment to the agricultural plan, almost six times (6.25), which will increase the probability of marketing the crop to the state compared to the commercial one. The other variable was the provision of loans with a double degree of about (2.72). The research concluded that paying attention to the aspect of financing and providing agricultural loans to farmers will lead to farmers getting rid of the financial restrictions imposed on them by the private sector. Also, the continuation of providing support will lead to an improvement in the level of farm income for farmers and not to search for other means to obtain income and thus adhere to the government legislation drawn up. The research recommended the need to provide government support and use modern technologies to increase production rates and achieve greater returns for farmers, and the presence of a supervisory body working to ensure that farmers do not violate the imposed government legislation.